Thermodynamic Evaluation of Gas/Steam Combined Cycle Performance With Active Controlled Film Cooling - Kumar, Sanjay; Singh, Onkar (Distributed Generation & Alternative Energy Journal, 2014)
Efficiency of gas turbine cycles can be improved by increasing the turbine inlet temperature. Advanced gas turbines operate at temperatures far above their material limitations to increase thermal efficiency. So, film cooling technique is mostly used to protect the gas turbine blades from high temperature gases. The film cooling jets penetrate into the mainstream gas and form a thin film for protecting the blade surfaces from hot gas. However, due to lift-off effect the attachment of the coolant jet to the blade wall, downstream, becomes crucial. Plasma actuator strategy proposed by some of the researchers may be considered to be utilized, to maintain the attachment of jet with the blade-wall and improve the film cooling effectiveness. In this article the effect of a proposed active controlled film cooling technique using plasma actuator strategy on thermodynamic performance of gas/steam combined cycle has been evaluated and compared with the combined cycle employing simple film cooling technique as well as with advanced transpiration cooling technique of gas turbine blades. Reduced coolant requirement and hence reduced dilution losses with active controlled film cooling as compared to simple film cooling, results in improved topping as well as bottoming cycle performance. It is seen that the combined cycle efficiency with active film cooling is comparable to the transpiration cooled combined cycle efficiency. At a turbine inlet temperature (TIT) of 1900 K, the combined cycle efficiency with active film cooling strategy is higher by 0.5% than that with simple film cooling.